The miracle of the bells [videorecording (DVD)] - Sinatra, Frank, 1915-1998; MacMurray, Fred, 1908-1991; Valli, Alida, 1921-2006; Cobb, Lee J., 1911-1976; Janney, Russell, 1884-1963 (Olive Films, 2013)
A young aspiring actress dies after making her first movie. Granting her final request, a Hollywood press agent brings the body of the actress, who died after making her first and only film, back to her hometown to be buried. To arouse public interest, and to get the reluctant studio head to release the film, he asks all the local churches to ring their bells for three days.